Predicting sports injuries in college soccer players: Insights from physical characteristics, fatigue, and performance trends - Yoshida, N.; Koido, M.; Kobayashi, T.; Nakamura, M.; Dohi, M.; Waki, H.; Mashimo, S.; Kato, H. (Sports Orthopaedics and Traumatology, 2025)
Summary Background: We investigated the relationship among physical characteristics, fatigue, and performance trends in male college soccer players to identify factors influencing sports injuries. Material and methods: Male college soccer players (N=168) subjectively evaluated their daily fatigue levels using a Visual Analog Scale. Coaches recorded weekly performance ratings. Sports injuries were categorized based on location, type, severity, occasion, and cause. Logistic regression with stepwise selection was used for analysis. Results: Seventy-three percent of injuries were traumatic, with the ankle joint being the most common injury site. Joint sprains accounted for the majority of injuries, with moderate cases being the most prevalent. The final logistic regression model identified seven explanatory variables, two of which were statistically significant at the 5% level: "total fatigue level 2 weeks ago" and "standard deviation of body mass index 2 weeks ago." Conclusions: By monitoring fatigue levels and body mass index, sports injuries may be predicted, enabling comprehensive injury prevention strategies, including tailored training programs and nutritional optimization. Zusammenfassung Hintergrund: Wir haben das Zusammenwirken von körperlichen Eigenschaften, Erschöpfung und Leistungstrends bei männlichen College-Fußballern untersucht, um Einflussfaktoren für die Entstehung von Sportverletzungen zu identifizieren. Material und Methoden: Männliche Fußballspieler (N = 168) bewerteten subjektiv ihre täglichen Erschöpfungsniveaus auf einer visuellen Analogskala. Trainer erfassten wöchentliche Leistungsbeurteilungen. Sportverletzungen wurden basierend auf Körperstelle, Typ, Schwere, Anlass und Ursache kategorisiert. Für die Analyse wurde logistische Regression mit schrittweiser Selektion angewendet. Ergebnisse: 73% der Verletzungen waren traumatischer Natur, die am häufigsten betroffene Körperstelle war das Sprunggelenk. Die am häufigsten verzeichneten Verletzungen waren, zumeist moderate, Gelenkverstauchungen. Das finale logistische Regressionsmodell identifizierte sieben unabhängige Variablen, von denen zwei eine statistische Signifikanz auf der 5%-Ebene aufwiesen: "der Gesamterschöpfungsgrad vor zwei Wochen" und "die Standardabweichung vom Body Mass Index vor zwei Wochen". Schlussfolgerungen: Sportverletzungen können durch eine Überwachung des Erschöpfungsniveaus und des Body Mass Index prognostiziert werden. Dies ermöglicht die Etablierung von umfassenden Präventionsstrategien mit angepassten Trainingsprogrammen und Ernährungsoptimierung.